Physiological response, testicular function, and health indices of rabbit males fed diets containing phytochemicals extract under heat stress conditions (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The present study aimed to evaluate the impact of dietary turmeric or garlic extract on physiological responses, hematological parameters, antioxidants status, testicular functions, and health indices of heat-stressed rabbit males.  Materials and Methods: Seventy bucks were distributed into seven experimental groups (ten/ group). A commercial diet (CD) was fed to rabbit males in the control group, while males in G2, G3, and G4 were fed CD with turmeric at 30, 60, and 90 mg/kg, respectively. Males in G5, G6, and G7 were fed CD with garlic extract at 50, 75, and 100 mg/kg, respectively, for 8 weeks.  Results: The results showed that turmeric or garlic extract levels decreased ear temperature, respiration rate, germ cell apoptotic number, total cholesterol, triglycerides, malondialdehyde level, libido, and sperm of dead and abnormal tail (p < 0.05). The hemoglobin and red and white blood cells, platelets, total antioxidants capacity, mass motility, mitochondrial potential, normal, acrosome reacted, normality, and a total functional fraction of spermatozoa and relative of epididymal weight were increased (p < 0.05). The increased packed cell volume percentage and initial semen fructose were significant only when 100 mg per kg garlic extract was supplemented.  Conclusion: Phytochemicals extract supplementation can be an effective dietary supplementation to eliminate heat stress and improve health, oxidative capacity, and testicular functions of rabbit males.J. Adv. Vet. Anim. Res., 8(2): 256-265, June 2021